Parental behaviour in autumn-staging Pink-footed Geese Anser brachyrhynchus - Tombre, Ingunn M.; Kristoffersen, Henrik; Madsen, Jesper (Wildfowl, 2025)
Goose parental behaviour is costly and represents a compromise between an individual’s need to spend time and resources maintaining its own body condition and survival with that required to successfully rear young. Geese are long-term monogamous species, with pair members cooperating to maximise their fitness outcomes by contributing differentially in time and function to the success of breeding attempts. For instance, enhanced male alertness during the reproductive season contributes to predator detection, whilst defending territories and broods from conspecifics also helps increase reproductive success. Such behaviour supports the female, which faces the high energy demands involved in producing and incubating eggs, by enabling her to spend more time foraging before, during and after the nesting period. Males also need to rebuild body stores after spending less time foraging during a period of heightened alertness, but this will be less marked than for the female following incubation. Hence, the time spent feeding and alert by parents would be expected to be more similar during autumn migration than during the breeding season, although both parents would be predicted to be more alert and to feed less than goslings, so that the still-growing young could maximise their food intake. To test these hypotheses, we observed the behaviour of individual Pink-footed Geese Anser brachyrhynchus, which were autumn-staging on spilt grain in stubble fields in central Norway. As predicted, there were no significant differences between female and male parents in the time spent foraging, alert or being aggressive towards conspecifics. Time spent by the parents on preening and sleeping were also similar for both sexes. Goslings and adult geese without young spent significantly more time foraging and less time alert than parental geese. On considering behaviour patterns in relation to the time of day, all geese were found to spend significantly more time foraging during the evening. We conclude that the behaviour of Pink-footed Geese at an autumn staging site, on their way to their wintering areas, reflects their age and breeding status, which may have positive fitness consequences.